2010
DOI: 10.1016/j.socscimed.2010.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant generation and physical activity among Mexican, Chinese & Filipino adults in the U.S.

Abstract: Migrant studies of physical activity (PA) can provide insight into the prevention of chronic disease. It is unclear, however, whether PA increases or decreases the longer migrants live in their host country. In the US, studies on immigrants' length of residence in the US and PA are inconclusive and many studies do not adequately consider the role of socioeconomic status (SES). Using California data, we examine relationships between immigrant generation and physical activity (PA) among Mexican, Chinese and Fili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(91 citation statements)
references
References 45 publications
5
82
1
1
Order By: Relevance
“…Specifically, a longer time in the country (10yrs +) [39,40], later generations (being born and having parents born in the new country) [41] and citizenship in the new country [42] also suggested an association with higher participation rates. Studies that evaluated reasons for immigration found that refugee populations suffered post-traumatic stress and were not considering or actively participating in physical activity [43,44] .…”
Section: Correlatesmentioning
confidence: 99%
“…Specifically, a longer time in the country (10yrs +) [39,40], later generations (being born and having parents born in the new country) [41] and citizenship in the new country [42] also suggested an association with higher participation rates. Studies that evaluated reasons for immigration found that refugee populations suffered post-traumatic stress and were not considering or actively participating in physical activity [43,44] .…”
Section: Correlatesmentioning
confidence: 99%
“…2327,37,48,86,87 This evidence from the health literature is not surprising given the heterogeneity of acculturation and assimilation processes in US immigrants, which scholars of migration have described. 88 Our study adds to the evidence on the adverse associations between accumulating exposure to US environment and diabetes risk and other health indicators in immigrants to the United States.…”
Section: Discussionmentioning
confidence: 97%
“…We classified a foreign-born respondent as a first-generation immigrant and a US-born respondent with at least 1 foreign-born parent as second generation; if the respondent and both parents were born in the United States, we classified him or her as third generation. 47,48 …”
Section: Methodsmentioning
confidence: 99%
“…It is well known that upon arrival to the US, immigrants are often healthier that those born in the US with lower body mass indexes, higher fruit and vegetable consumptions, and higher levels of certain physical activities [68][69][70][71][72][73][74][75]. An explanation for these health advantages in first generation immigrants is their maintenance of the cultural beliefs stemming from their country of origin.…”
Section: Future Directionsmentioning
confidence: 99%